Peer effects and debt accumulation: Evidence from lottery winnings - Magnus A. H. Gulbrandsen (Norges Bank, 2021)
I estimate the effect of lottery winnings on peers' debt accumulation using administrative data from Norway. I identify neighbors of lottery winners, and estimate an average debt response of 2.1 percent of the lottery prize among households that live up to ten houses from the winner. Analyzing heterogeneity, I find that neighborhood characteristics and shared characteristics with the winner matter for the debt response: there is a tendency for greater effects for those (1) residing closest to the winner, (2) residing in single-household dwellings, (3) with a longer tenure, and (4) with a household structure similar to that of the winner. Finally, estimates of the (imputed) expenditure response among neighbors indicate that they accumulate debt to finance increased spending, consistent with a "keeping-up-with-the Joneses" type explanation, where neighbors react to each others expenditure.
hdl:11250/2827721
Keywords: D14; D31; D91; E21; G51; 330; peer effects; debt accumulation; income shocks; network homophily; household finance